Thymus lotocephalus wild plants and in vitro cultures produce different profiles of phenolic compounds with antioxidant activity - Costa, Patrícia (2013)
We compared the phenolic metabolites and antioxidant activities of Thymus lotocephalus G. López & R.Morales wild plants and in vitro cultures using different extraction solvents. HPLC–DAD analysis allowed the identification and quantification of phenolic (caffeic and rosmarinic) acids and flavones (luteolin and apigenin) in extracts from both sources. The in vitro cultures accumulated large amounts of rosmarinic acid. However, extracts from both sources were able to neutralise free radicals in different test systems(TEAC and ORAC assays), to form complexes with Fe2+ and to protect mouse brains against Fe2+-induced lipid peroxidation. The solvent significantly influenced the phenolic content and antioxidant activity of the extracts, water/ethanol being the most efficient for the extraction of antioxidant phytochemicals. We conclude that in vitro cultures of T. lotocephalus represent a promising alternative for the production of valuable natural antioxidants and an efficient tool for the in vitro biosynthesis of rosmarinic acid, therefore avoiding the need to exploit populations of wild plants.